Aboriginal Voter Turnout in Northern Saskatchewan - Loleen Berdahl; Greg Poelzer; Bonita Beatty (aboriginal policy studies, 2012)
Research to date on Aboriginal electoral participation - and the participation of Métis and off-reserve First Nations in particular - remains quite limited, leaving those policy makers and groups seeking to increase Aboriginal voter turnout to make assumptions about Aboriginal voter turnout that may or may not be valid. Drawing on original quantitative survey data collected in northern Saskatchewan, the authors of this paper demonstrate that Aboriginal groups differ from each other in federal voter turnout; that the federal turnout differences between on-reserve First Nations and Métis peoples (but not on- and off-reserve First Nations) largely reflect socio-demographic differences; and that on-reserve First Nations are less likely to report federal voting than non-Aboriginal peoples, even after other variables are taken into account. The authors suggest that it is important to consider local context and history in addition to socio-demographic and “voting resource” variables in order to understand - and, potentially, to increase - Aboriginal federal turnout levels.